Perfluorocarbon@Porphyrin Nanoparticles for Tumor Hypoxia Relief to Enhance Photodynamic Therapy against Liver Metastasis of Colon Cancer - Liang, Xiaolong; Chen, Min; Bhattarai, Pravin; Hameed, Sadaf; Dai, Zhifei (ACS nano, 2020)
Photodynamic therapy (PDT) shows great promise for the treatment of colon cancer. However, practically, it is a great challenge to use a nanocarrier for the codelivery of both the photosensitizer and oxygen to improve PDT against PDT-induced hypoxia, which is closely related to tumor metastasis. Hence, an effective strategy was proposed to develop an oxygen self-supplemented PDT nanocarrier based on the ultrasonic dispersion of perfluorooctyl bromide (PFOB) liquid into the preformed porphyrin grafted lipid (PGL) nanoparticles (NPs) with high porphyrin loading content of 38.5%, followed by entrapping oxygen. Interestingly, the orderly arranging mode of porphyrins and alkyl chains in PGL NPs not only guarantees a high efficacy of singlet oxygen generation but also reduces fluorescence loss of porphyrins to enable PGL NPs to be highly fluorescent. More importantly, PFOB liquid was stabilized inside PGL NPs with an ultrahigh loading content of 98.15% due to the strong hydrophobic interaction between PGL and PFOB molecules, facilitating efficient oxygen delivery. Both in vitro and in vivo results demonstrated that the obtained O2@PFOB@PGL NPs could act as a prominent oxygen reservoir and effectively replenish oxygen into the hypoxic tumors with no need for external stimulation, conducive to augmented singlet oxygen generation, hypoxia relief, and subsequent downregulation of COX-2 expression. As a result, the use of O2@PFOB@PGL NPs for hypoxia relief dramatically inhibits tumor growth and liver metastasis in an HT-29 colon cancer mouse model. In addition, the O2@PFOB@PGL NPs could serve as a bimodal contrast agent to enhance fluorescence and CT imaging, visualizing nanoparticle accumulation to guide the subsequent laser irradiation for precise PDT.